Network models and optimization : multiobjective genetic algorithm approach - Gen, Mitsuo , 1944-; Cheng, Runwei; Lin, Lin (Decision engineering, 2008)
Network models are critical tools in business, management, science and industry. This book presents an insightful, comprehensive, and up-to-date treatment of multiple objective genetic algorithms to network optimization problems in many disciplines